2014
DOI: 10.1111/apm.12302
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying fibrous tumor: an unrecognized IgG4—related disease?

Abstract: Calcifying fibrous tumor is a rare benign mass lesion characterized by bland spindle cells embedded in abundant collagenous matrix, interspersed dystrophic or psammomatous calcifications, and lymphoplasmacytic infiltrate. It shares several clinical and morphologic features with IgG4-related disease, a newly recognized fibroinflammatory disorder. Characteristic histologic features of IgG4-related lesions include dense fibrosis and abundant lymphoplasmacytic infiltrate, similar to calcifying fibrous tumor. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Furthermore, there are several articles in the English medical literature in which it is reported that CD34, CD68, IgG, and IgG4 can be occasionally focally expressed in mast cells of CFT. 99 , 106 Larson et al 66 mentioned that CFT shares certainly some morphologic features with an IgG4-related disease, as they found increased IgG4 in serum of a patient with CFT. Based on the sex predominance of these tumors, we believe that further study should be done on sex hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are several articles in the English medical literature in which it is reported that CD34, CD68, IgG, and IgG4 can be occasionally focally expressed in mast cells of CFT. 99 , 106 Larson et al 66 mentioned that CFT shares certainly some morphologic features with an IgG4-related disease, as they found increased IgG4 in serum of a patient with CFT. Based on the sex predominance of these tumors, we believe that further study should be done on sex hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…No recurrences or metastasis are observed, except for 6 cases of patients who appeared with a recurrence within their follow-up period, including 2 cases of neck CFT in an infant, 2 cases of neck CFT in 3-year-old children, 1 case of small intestine CFT in 43-year-old man, who also had a metastasis, and 1 case of upper extremities CFT in an 1-year-old child. 2 , 10 , 11 , 21 , 28 , 33 , 66 , 81 More than 88% of the patients are cured by the local surgical excision of the tumor. No deaths have been noted owing to CFT and long-term survival of patient seems to be certain.…”
Section: Discussionmentioning
confidence: 99%
“…Larson et al . [ 10 ] also suggested that CFT could be an IgG4 related disease. Although these reports support that CFT might be IgG4 related, our case was negative for IgG4 stain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that CFT may fall within the spectrum of IgG4related disease. 47,48 However, this is not widely accepted. Pleural CFT occurs predominantly in adult women.…”
Section: Calcifying Fibrous Tumormentioning
confidence: 99%